Pelatihan Screen Printing Berbasis Produksi Sebagai Peningkatan Kompetensi Siswa SMK di Dunia Industri - Rahman Soesilo; Suryo Sulistyo; Abdul Rasyid; Esta Larosa (Universitas Negeri Gorontalo, 2023)
In conclusion, the Production-Based Screen Printing Training to Increase the Competence of Vocational High School Students in the Industry is a significant program that aims to enhance the vocational skills of students in the industry. The significance of screen printing training lies in its ability to provide students with practical knowledge and hands-on experience in producing high-quality prints. Through production-based training, students are exposed to real-life scenarios that prepare them for the demands of the industry. This type of training also helps develop their problem-solving skills and critical thinking abilities. moreover, integrating screen printing into the industry is crucial as it provides a cost-effective method for producing high-quality prints. It also opens up opportunities for students to pursue careers in various industries such as fashion, advertising, and graphic design. Overall, Production-Based Screen Printing Training to Increase the Competence of Vocational High School Students in the Industry is an excellent initiative that benefits both students and industries alike. It equips students with essential vocational skills while providing industries with a skilled workforce capable of meeting their demands.